The Poseidon project the struggle to govern the world's oceans - Bosco, David L. (New York, NY Oxford University Press, 2022)
For several centuries, freedom of the seas was the dominant framework for managing the oceans and their use. That doctrine recognized the oceans as a space open to all, which people from all nations could use and exploit. In recent decades, however, that doctrine has eroded in multiple ways and for a variety of reasons. During the world wars of the 20th century, combatants imposed unprecedented restrictions on maritime commerce, leaving international rules in tatters. National governments have steadily expanded their reach into the oceans. More recently, environmental concerns have led to new international restrictions on high seas pollution and fishing. Today's most dangerous maritime disputes-including China's push for control of the South China Sea-are occurring against the backdrop of major changes in the way the world treats the oceans. Tracing the roots of the law of the sea and the background to current maritime disputes, this book shows that building effective ocean rules while preserving maritime freedoms remains a daunting task. The book analyzes how fragile international institutions and determined activists are struggling for relevance in a world still dominated by national governments"--
Introduction -- The global ocean (to the 1700s) -- Britannia's rules (1750-1914) -- The unraveling (1914-1945) -- Adrift (1945-1970) -- The ocean constitution (1970-1982) -- Jockeying for position (1982-1995) -- The convention in operation (1995-2010) -- System under strain (2010-present) -- Conclusion : sea changes.
Includes bibliographical references (pages 249-292) and index.
Keywords: Electronic books -- Law of the sea -- History